BOUNDEDNESS AND EXISTENCE ANALYSIS SOLUTION OF AN OPTIMAL CONTROL PROBLEMS ON MATHEMATICAL COVID-19 MODEL - Hakim, Lukman; Widayanti, Lilis (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
The investigation given right here is part of a literature review on mathematical models that apply analytical mathematics. The present work focuses on the COVID-19 model, which incorporates optimum control variables previously investigated and interpreted by Hakim. Depending on the current model, we will further develop the analysis and demonstrate the non-negativity condition as well as the boundedness criteria for the solutions. Additionally, we conduct several supplementary analyses by applying the Lipschitz function to examine the uniqueness of the solutions and the existence of the solution are hold on the autonomous system. This work to supports the previously findings that incorporating an optimal control into the model can reduce COVID-19 treat on public. Finally, that research verifies that the control variables used in the research satisfy all of the existence criteria, as outlined in Theorem 5 of this work.